EFEKTIVITAS PEMANFAATAN PAPAN INTERAKTIF DIGITAL (PID) UNTUK MENINGKATKAN KEMAMPUAN LITERASI PADA SISWA DI UPT SD NEGERI 13 SILORO KABUPATEN PANGKAJENE DAN KEPULAUAN - Nurhayana; Muthiyah Salsabilah; Mutmainnah; Tarman A. Arif (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the effectiveness and the process of utilizing Digital Interactive Boards (DIB) to improve students' literacy skills at UPT SD Negeri 13 Siloro, Pangkajene and Kepulauan Regency. The core problem is identified by the students' low ability to comprehend implicit text meanings and the presence of students who have not achieved formal reading fluency. This study employed a descriptive qualitative approach. The location was determined purposively based on the availability of technological facilities supporting the digitalization of learning. The research subjects included the classroom teacher, fourth-grade students, and the school’s infrastructure/IT coordinator. Data collection techniques involved method triangulation comprising participant observation, in-depth interviews, and document reviews. Supporting instruments consisted of interview guides, observation sheets, and field notes. Data analysis applied the Miles and Huberman interactive model, which includes data reduction, data display, and conclusion drawing. The results demonstrated that the utilization of DIB significantly reduced the percentage of reading incomprehension from 20% to 5% and accelerated the reading fluency of 4 out of 7 previously struggling students. This success was driven by the integration of audiovisual features, kinesthetic stimulation through touch interactivity, and gamification elements capable of reducing learning anxiety.